IMPLEMENTATION OF THE PROMOTION MIX AT MUARA TAKUS TEMPLE XIII KOTO KAMPAR DISTRICT KAMPAR SUB-DISTRICT RIAU PROVINCE - Swaperi, Sabila Adiputra; Arief, Andi M Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research is to know how the implementation of the promotion mix at Muara Takus Temple XIII Koto Kampar District Kampar Sub-District Riau Province.This research uses a quantitative method with a descriptive approach to describe the actual state by collecting data and information in the field. The sample in this research as many as 100 were taken using census sampling. While data collection techniques in this research use observations, questionnaires, interviews, and documentation. By using a Likert scale as a measuring instrument determines the length of the short interval.Based on the research that has been done, tourists responses on the implementation of the promotion mix at Muara Takus Temple XIII Koto Kampar District Kampar Sub-District Riau Province, about advertising, sales promotion and publicity is not good enough and not run the proper promotion planning strategy.Key words : Promotion Mix, Muara Takus Temple.